Lubricating and Conductive Properties of Modified Graphene/Silver Nanoparticles Under Current-Carrying Friction Conditions - Yuxin Chen; Kun Peng; Xiao Li; Luyi Sun; Taiyu Su; Wei Zhang; Dancong Zhang; Shiwei Fan; Hongbin Yin; Ming Zhou (Lubricants)
With the rapid development of the electric vehicle industry, motor bearings have higher requirements for the friction reduction and electrical conductivity of grease. The addition of lubricant additives to improve the interfacial state is an effective method for enhancing both lubrication and electrical conductivity. In this study, graphene (G) and silver nanoparticles (AG) were modified using ionic liquids (ILs) to prepare additive ionic liquid/graphene/silver nanoparticles (GILAG) with good performance. GILAG was incorporated into the grease, and the current-carrying friction test results demonstrated significant improvements in both lubrication and electrical conductivity, with a 63.66% decrease in contact resistance relative to the base grease. These excellent properties are mainly attributed to the synergistic effect between the G, IL, and AG in GILAG, which improves the interfacial state, promotes lubricity, and enhances the electrical conductivity of the friction interface. This work provides new conceptual bases for the design of conductive lubrication additives.